Differential and synergistic actions of nerve growth factor and cyclic AMP in PC12 cells (The Rockefeller University Press, 1981)
When a clonal line of rat pheochromocytoma (PC12) was exposed to beta- nerve growth factor (beta NGF), N6, O2-dibutyryl adenosine 3':5' cyclic monophosphate (Bt2cAMP), or a combination of the two, 10, 26, or 70% of the cell clumps, respectively, displayed neurites after 1.d. Increases in the cellular RNA concentration were also found to be additive or greater when both agents were present. Neurites induced by Bt2cAMP alone were not maintained after replacement with beta NGF. The degree of potentiated neurite outgrowth was a function of the time of simultaneous exposure to both agents. The initiation of neurite outgrowth in the presence of Bt2cAMP was independent of RNA synthesis, in contrast to that induced by beta NGF alone. We conclude that beta NGF-induced initiation of morphological differentiation of these cells is not mediated by a cAMP-dependent mechanism. Consideration of Bt2cAMP effects upon other cell lines suggest that Bt2cAMP causes a rapid, but unstable, reorganization of the PC12 cytoskeleton, resulting in the initiation of neurite outgrowth from these cells. In contrast, beta NGF alone achieves a more stable cytoskeleton reorganization by an RNA synthesis-dependent mechanism.